Implementasi Kebijakan Pemerintah Atas Perluasan Ganjil Genap Terhadap Aktivitas Logistik di Wilayah DKI Jakarta - Tri Mulyani Setyowati; Yogi Ashari; Erni Pratiwi Perwitasari (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
This research aims to identify the impact of delivery in full, on time (DIFOT), just in time (JIT), and logistics costs due to the expansion of odd-even policy on logistics activities in DKI Jakarta. This research used primary data obtained from the questionnaire distributed to business people in the logistics sector. The instrument model used in this study was multiple linear regression. The result shows that the three variables, which were delivery in full, on time (DIFOT), and just-in-time (JIT), has strong (significant) impacts on logistics activities. On the other hand, logistics cost has less impact on logistics activities since anticipation could still be done by hiring outsourcing partners for transportation vehicle units and adjusting distribution times for areas affected by odd-even policy.